3D annotation in contemporary dance: enhancing the creation-tool video annotator - Ribeiro, C.; Kuffner, R.; Fernandes, C.; Pereira, J. (Proceedings of the 3rd International Symposium on Movement and Computing, 2016)
Annotated videos have been used in the context of dance performance not only as a way to record and share compositions and knowledge between different choreographers, but also as a powerful learning tool. Restraining the viewpoint of the user to the recorded point of view can be an obstacle in several scenarios. Alternatives that introduce the concept of a three-dimensional space have been developed, but coming short either on the freedom of concepts that the user is able to introduce, or on resorting to a non-natural representation. This article describes a follow-up work on the previously developed Creation-Tool [2] extending the existing functionality to tackle this problem. The developed system places the 2D annotations onto a three-dimensional point cloud, captured by depth sensors coupled with cameras around the performance, thus enabling the user to freely visualize the annotated performance three-dimensionally at an arbitrary point of view.